Legal Aspects & Evaluation of Operational Service Performance Standards of Boom Baru Container Terminal Palembang - Tulus Umy Purwati; Erika Buchari; Edi Kadarsah (Jurnal Akta, 2020)
This research was conducted to evaluate legal aspects and the service performance of the Boom Baru Palembang Container Terminal has implemented the DIRJENHUBLA Standard. The research was conducted by collecting data from the Boom Baru Container Terminal and then calculating and evaluating based on applicable regulations. Performance analysis is carried out by calculating BOR (Berth Occupancy Ratio), YOR (Yard Occupancy Ratio), BTP (Berth Troughput), and Effective Time Ratio (ET: BT). Performance analysis shows that the 2018 for BOR value does not match the rules which is 58.57% and it is above the UNCTAD recommended value of 50% and the 2019 BOR value of 48.36%. The 2018 Effective Time Ratio (ET: BT) value of 55% is under minimum DIRJENHUBLA standard of 70%.